Web-Based Online Reservation System With The Implementation Of The First Come First Served (FCFS) Algorithm To Overcome Customer Queues At A Barber Shop In Bandung - Susanto Susanto; Yangyang Yangyang; En tay (JURNAL COMPUTECH & BISNIS, 2025)
With the rising demand for digital services, industries such as barbershops must utilize technology to improve service efficiency, especially in controlling customer lineups.  Kabarbershop currently uses a manual queueing system, resulting in unpredictable wait times, potential customer attrition, and inaccuracies in documentation.  This study creates a web-based Online Reservation System that uses the First Come First Served (FCFS) algorithm to efficiently and equitably manage queues.  The study employs the Research and Development (R&D) methodology, using a Waterfall development strategy.  The system is architected with Unified Modeling Language (UML) and developed using Next.js for the frontend, Tailwind CSS for a responsive UI, ExpressJS for the backend, and MongoDB as the database.  Essential features include online bookings, wait-time assessment, WhatsApp alerts, and an administrative dashboard.  Findings from black box testing demonstrate that all functionalities perform as anticipated.  This system aims to improve operational efficiency, minimize customer attrition, and offer a more convenient and transparent reservation experience.